2018
DOI: 10.1016/j.pharep.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic and anti-inflammatory effects of long-circulating liposomes co-encapsulating curcumin and doxorubicin on C26 murine colon cancer cells

Abstract: LCL-CURC-DOX demonstrated enhanced cytotoxicity on C26 murine colon cancer cells by inhibiting the production of the majority of factors involved in tumor-associated angiogenesis and inflammation and is now being evaluated in vivo regarding its efficacy towards tumor growth in colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Liposomal curcumin was prepared as PEG-coated nanoliposomes using the film hydration method, as previously described. 23 Briefly, the phospholipids were used in a concentration of 70 mM, of which 66.5 mM DPPC, the main lipid, and 3.5 mM PEG-2000-DSPE, a PEG-derived phospholipid, to achieve long circulation properties and an increased therapeutic efficiency. Cholesterol was added to the lipid mixture in 10:1 phospholipids to cholesterol molar ratio.…”
Section: Preparation Of Liposomal Curcuminmentioning
confidence: 99%
“…Liposomal curcumin was prepared as PEG-coated nanoliposomes using the film hydration method, as previously described. 23 Briefly, the phospholipids were used in a concentration of 70 mM, of which 66.5 mM DPPC, the main lipid, and 3.5 mM PEG-2000-DSPE, a PEG-derived phospholipid, to achieve long circulation properties and an increased therapeutic efficiency. Cholesterol was added to the lipid mixture in 10:1 phospholipids to cholesterol molar ratio.…”
Section: Preparation Of Liposomal Curcuminmentioning
confidence: 99%
“…Thus, the release of IL-1ra by POS-stimulated may help to protect the synthetic metabolic environment of the natural cartilage during bone cartilage repair. POS activating STAT-1 and -3 signaling pathways will not be beneficial to CC control while the increase of anti-inflammatory cytokines will result in the prevention of CC ( 37 , 92 ).…”
Section: Pos Affect Mitogen-activated Protein Kinases (Mapk) Signalinmentioning
confidence: 99%
“…Previous studies have reported that curcumin inhibits the activity of inducible NOS of intestinal tract. Curcumin can also inhibit the production of many proinflammatory cytokines by inhibiting the activity of inducible NOS, which can alleviate the inflammatory reaction of mice with multidrug resistance gene deficiency, alleviate the development of colitis induced by sodium dextran sulfate, and inhibit the production of many proinflammatory cytokines [6] . NO free radicals and superoxide anions were effectively eliminated, and oxidative stress and acute gastric injury were alleviated [7] .…”
Section: Discussionmentioning
confidence: 99%